Hermetia illucens oil vs. hydrogenated palm fat in dairy cow nutrition: effects on digestive parameters, oxidative stress, and milk production performance - Rastello, Lara; Gasco, Laura; Coppa, Mauro; Gerbelle, Mathieu; Colombini, Stefania; Battelli, Marco; Badino, Paola; Vernetti-Prot, Luca; Toral, Pablo G.; Brugiapaglia, Alberto; Gardini, Giulia; Malfatto, Vanda; et al. (Journal of animal science and biotechnology, 2025)
Background Scant information is currently available on the use of insect oils in ruminant diets. Insect oils could be used as alternatives to certain conventional plant lipid sources that are considered no longer sustainable. This trial aims at evaluating the effects of the dietary inclusion of Hermetia illucens oil (HIO) vs. hydrogenated palm fat (HPF) on digestive parameters, oxidative stress, and milk production performance of dairy cows. Results Twenty-six Valdostana Red Pied cows were randomly divided into two groups and fed with hay ad libitum and a concentrate containing 3% (as fed) of either HPF or HIO. The trial lasted 50 d, including two weeks of diet adaptation. Individual feed intake and milk yield were monitored three and four times a week, respectively. Fecal samples were collected at the end (d 50) of the trial to determine total-tract nutrients apparent digestibility. Individual blood samples were collected to evaluate blood plasma metabolites (d 0 and d 50) and oxidative stress parameters (d 0, d 26 and d 50). Milk samples were collected at d 0, d 14, d 26, d 38 and d 50 for chemical composition analysis. Feed efficiency was estimated through feed conversion ratio and residual feed intake (RFI). Data were analyzed by SAS software using a mixed model. The diet had no effect on nutrients intake and apparent total-tract digestibility. However, the dietary inclusion of HIO led to higher milk production (+ 0.82 kg/cow/d; P < 0.05) and slightly lower RFI (−0.008; P < 0.001) when compared to the HPF diet. Milk composition and the nutritional metabolic status of the cows remained unaffected by diet. Serum antioxidant capacity was comparable between the two groups, while lower derivatives of reactive oxygen metabolite concentrations were observed in the HIO-fed cows when compared to the HPF-fed ones (−37.13 Carratelli Units; P < 0.001). Conclusions The dietary inclusion of HIO instead of HPF did not negatively affect feed palatability and total-tract apparent digestibility of nutrients in dairy cows. Furthermore, it increased feed efficiency by supporting a higher milk production together with an improved antioxidant status. The results suggest that HIO could be an eligible option as an innovative energy source for dairy cows.